Qur’anic Insights on Educational Evaluation: A Semantic Study - Zainuddin, Fauziah; Che Hat, Norhayati (Institut Agama Islam Negeri (IAIN) Kendari, 2025)
While numerous studies have examined educational evaluation from Islamic perspectives, limited scholarly attention has been directed toward its semantic foundations in the Qur’an. This study explores the concept of educational evaluation by conducting a semantic analysis grounded in Toshihiko Izutsu’s theoretical framework. Adopting a qualitative case study design with an interpretative approach, the research investigates key Qur’anic terms and expressions related to evaluation, focusing on their basic meanings, contextual relationships, and placement within broader semantic fields. The analysis reveals five core concepts underpinning Qur’anic views on educational evaluation: ḥisāb (accountability), wazan (weighing), taqwīm (assessment/upliftment), fitnah (trial), and ibtilāʾ (testing). These concepts construct a comprehensive evaluative paradigm that challenges pre-Islamic (Jāhilī) norms, which emphasized collective over individual responsibility, privileged status over intrinsic value, and material misfortune as divine condemnation. In contrast, the Qur’anic discourse promotes a framework of evaluation that centers on moral intention, personal accountability, and holistic human development. This semantic study thus calls for a reconfiguration of educational evaluation within Islamic contexts, moving beyond mechanistic measurements toward ethically rooted, spiritually conscious, and pedagogically transformative practices. The findings offer practical implications for the design of Islamic education curricula and evaluation tools that align with Qur’anic values while addressing contemporary educational needs